Disinfection studies of Nahar (Mesua ferrea) seed kernel oil using pour plate method - Adewale, Ahmed Idris; Mirghani, Mohamed Elwathig Saeed; Muyibi, Suleyman Aremu; Daoud, Jamal Ibrahim; Mikail, Maryam Abimbola (Academic Journals, 2011)
As a result of disinfection byproducts (DBP) concerns from chlorine, Environmental Protection Agency (EPA) as well as the water treatment industry, place more emphasis on the use of disinfectants other than chlorine. Disinfection also plays a key role in the reclamation and reuse of wastewater for eliminating infectious diseases, and to augments domestic water supply and decrease the impact of human activities on the environment. The aims of this study were thus: to investigate the potential of the Nahar seed kernel oil (NSKO) as an alternative natural disinfectant, and to study its disinfection kinetics. Heterotrophic plate count, using CFU/ml, pour plate method, 35°C / 48 h, plate count agar were employed to evaluate the disinfection and its kinetics. The result obtained showed that NSKO has a remarkable disinfection potential and the kinetics studies suggested that NSKO fitted first-order model with a k value of -0.040.